An examination of the codes of ethics artefacts in top Taiwanese companies. (8th April 2009) - Lee, Tzong Ru; Svensson, G.; Wood, G.; Callaghan, M.
This study examines the use of codes of ethics artefacts among top companies in Taiwan. This research reports on the responses of those top Taiwanese companies that possessed a code of ethics. The empirical findings are compared to the findings of previous research. Top Taiwanese companies appear not to be drastically different from top companies in other countries in terms of the areas examined. Several similarities have been revealed. This study provides valuable insights into a previously unexplored corporate territory in terms of codes of ethics artefacts. Furthermore, it provides a seed and guidance for further research in other corporate cultures worldwide. Two parts of interest to business practices may be distinguished in terms of corporate codes of ethics artefacts, namely a regulatory one and one that supports staff. It also provides a valuable point of reference to previous research of corporate codes of ethics artefacts.